Success Factors in the Implementation of Healthcare Information Systems (HIS) among Developing Countries - Rahman, Shafiqur; Islam, Aminul (Bangladesh Journal of Medical Science, 2024)
Developing countries face significant challenges establishing healthcare information systems (HIS) due to inadequate government regulations and outdated technology infrastructures. For example, the lack of digital patient data collection in Bangladesh exacerbates the accessibility to quality healthcare. Standardizing hospital healthcare systems could streamline patient management, potentially servicing more patients effectively. This study utilizes a systematic literature review (SLR) to consolidate key factors enhancing HIS in such regions. By reviewing 4014 studies from databases like IEEE Xplore and Science Direct, the research identified 12 success criteria organized into four main themes, emphasizing the crucial role of resource allocation in deploying effective HIS. Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 957-966